PERANAN PERSERIKATAN BANGSA- BANGSA DAN AFRICAN UNION (AU) DALAM MENYELESAIKAN KONFLIK BERSENJATA NONINTERNASIONAL DI DARFU - Balqis Hanya Alfiana, Joko Setiyono*), Elfia Farida (Program Studi S1 Ilmu Hukum, Fakultas Hukum, Universitas Diponegoro, 2013)
Non-International armed conflict that occured in Darfur Sudan is the continued conflict between Northern Sudan and Southern Sudan. It seemed a coincidence that the Darfur crisis broke out soon after the signing of Machakos Protocol, 20 July 2002. The conflict involving the Sudan’s government aided militant group called the Janjaweed against the rebel Sudan Liberation Movement / Army (SLM / A) and the Justice Equality Movement (JEM) which is based on the struggle for natural resources between community groups Arab and groups nonArab who’s live in Darfur. Janjaweed accused of human rights violations, including torture, kidnapping, rape, looting and other. This became the international spotlight. Therefore, the United Nations (UN) and African Union (AU) decided to intervention in to Darfur conflict by acting as a mediator to reach a peace agreement between Sudan’s government, SLM/Aand JEM. The Sudanese government presurred by United Nations and the African Union to support ongoing Peacekeeping Operation. UNAMID managed to bring peace to the Sudan by signing the